Takaful as a Mechanism for Protecting Unsecured Creditors: Legal and Operational Considerations in Malaysia - Hazrai Afizi Che Haron Shafiee; Hartinie Abd Aziz; Zuhairah Ariff Abd Ghadas; Norizan Remli; Nurhidayah Abdullah (Yustisia, 2024)
In the mandatory winding-up procedure, all payments must be prioritised before disbursements to unsecured creditors, as the Malaysia Companies Act 2016 stipulated. Unsecured creditors, positioned lower in the hierarchy of creditors, may not recover the funds owed to them from the company's liabilities, resulting in financial hardship for these creditors. All unsecured creditors must demonstrate their claims following the issuance of the winding-up order. Nonetheless, the existence of debt evidence does not guarantee payment if the corporation lacks sufficient assets to satisfy unsecured creditors after addressing secured and preferential creditors. This article seeks to investigate the rights of the unsecured creditors during winding up and to analyse the possibility of establishing a new mechanism, specifically takaful (Islamic insurance), to protect the unsecured creditors during winding up. This study adopts a qualitative approach, employing doctrinal analysis and interviews with industrial stakeholders. This article highlights the need to implement takaful as a potential solution for unsecured creditors to recover their debt if the company is wound up